2016
DOI: 10.24014/ja.v6i2.2237
|View full text |Cite
|
Sign up to set email alerts
|

Peningkatan Efisiensi Pupuk Fosfat Melalui Aplikasi Mikoriza Pada Kedelai

Abstract: The research purpose to investigate effect of mychorriza and phosphor dosage on growth and yield of soybean. The research was conducted in field experimental of Agriculture and Animal Science Faculty of State Islamic Univesity of Sultan Syarif Kasim Riau started from April to July, 2015. The planting media was peat soil with a pH of 4,79 and seeds used black soybean Mallika Varieties .The research was used Randomized Block Design with two factorials and four replications, the first factor was the dosage phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
8
0
2
Order By: Relevance
“…AMF inoculations have not gone well on the number of pods, the number of hollow pods, and the weight of 100 soybean seeds. The results of Pernamasari et al (2016) research showed that the administration of AMF has no effect on the number of pods plants -1 , the number of seeds plants -1 , and the weight of dried seeds plants -1 , but the administration of amf more and more will increase crop yields as the dose of AMF given. The body is microorganism as well as MVA can release various organic compounds with various functions.…”
Section: Resultsmentioning
confidence: 99%
“…AMF inoculations have not gone well on the number of pods, the number of hollow pods, and the weight of 100 soybean seeds. The results of Pernamasari et al (2016) research showed that the administration of AMF has no effect on the number of pods plants -1 , the number of seeds plants -1 , and the weight of dried seeds plants -1 , but the administration of amf more and more will increase crop yields as the dose of AMF given. The body is microorganism as well as MVA can release various organic compounds with various functions.…”
Section: Resultsmentioning
confidence: 99%
“…In the growth of plant roots, the macronutrient P available in the soil will affect the growth rate of plant roots. The high element P in the soil can cause most of the photosynthetic results to be distributed more to the canopy for plant growth (Permanasari et al, 2016).…”
Section: Growth and Yield Of Cucumber Plants Against Dolomite Applica...mentioning
confidence: 99%
“…Kolonisasi akar sangat dipengaruhi oleh jumlah spora FMA yang ada di rhizosfer tanah dan tingkat kecocokan terhadap tanaman inang. Permanasari et al (2016) menyatakan bahwa kolonisasi FMA dalam akar tanaman dipengaruhi oleh jumlah spora. Semakin tinggi jumlah spora FMA maka tingkat koloni mikoriza pada akar tanaman yang ada di dalam tanah akan semakin banyak pula.…”
Section: Kolonisasi Dan Kepadatan Spora Fma Pada Akar Tanaman Kelapa ...unclassified